1984
DOI: 10.1073/pnas.81.14.4399
|View full text |Cite
|
Sign up to set email alerts
|

Picosecond fluorescence decay of tryptophans in myoglobin.

Abstract: The fluorescence decay characteristics of Mb, MbCO, metMb (sperm whale), metMb (yellowfin tuna), and their apo derivatives were determined by using a picosecond streak camera and time-correlated single photon counting. The emission is dominated by tryptophans that transfer their energy to the heme on a subnanosecond time scale. Sperm whale Mb and derivatives have two tryptophans and their decays can be interpreted mainly as two exponentials, one of ca. 20 ps and the other of 130 ps, whereas tuna Mb has one try… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
88
1

Year Published

1989
1989
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 122 publications
(94 citation statements)
references
References 44 publications
5
88
1
Order By: Relevance
“…This points to a long-lived change in the electrostatic environment of Trp 86 , which lends credence to an ''electrostatic conflict'' (15) To the best of our knowledge, tryptophans have been used in studies of photoinduced energy transfer (35) and electron transfer (36) in proteins, processes that are not or only indirectly related to their function, and as a probe of the solvation dynamics of the interfacial water layer on proteins (37). Here, we demonstrate their use as a reporter of the functional electric field changes within the protein in the course of its biological activity.…”
Section: Resultsmentioning
confidence: 99%
“…This points to a long-lived change in the electrostatic environment of Trp 86 , which lends credence to an ''electrostatic conflict'' (15) To the best of our knowledge, tryptophans have been used in studies of photoinduced energy transfer (35) and electron transfer (36) in proteins, processes that are not or only indirectly related to their function, and as a probe of the solvation dynamics of the interfacial water layer on proteins (37). Here, we demonstrate their use as a reporter of the functional electric field changes within the protein in the course of its biological activity.…”
Section: Resultsmentioning
confidence: 99%
“…The [47,48]. The fluorescence decay is dictated by the fast identity of some of the helices; however, as a whole, it represents a more flexible and disordered structure than the native energy transfer from the Trp to the heme, which suppresses all other nonradiative pathways of excited state relaxation.…”
Section: Methodsmentioning
confidence: 99%
“…The tryptophan fluorescence of the heme proteins is dominated by fast energy-transfer-/decay kinetics with lifetime components in the subnanosecond range (Hochstrasser and Negus, 1984). The efficiency of the energy transfer depends on the distance and the relative orientation of the heme and tryptophan residues, The relative orientation of the two chromophores is expressed through a quantity, IC' (see Materials and Methods).…”
Section: Solvent-accessible-area Calculationsmentioning
confidence: 99%
“…However, several studies have been reported on multi-tryptophancontaining proteins, such as myoglobin (Hochstrasser and Negus, 1984;Wills et al, 1990), hemoglobin (Szabo et al, 1984), cytochrome-c oxidase (Das and Mazumdar, 1994), cytochrome P-450,,, (Lange et al, 1994), cytochrome P-45OCzl, and bacteriorhodopsin (Albani et al, 1985;Godik et al, 1993). These studies have proved useful in investigating the nature of the environment around the fluorophore and the relative position of the energy-accepting group with respect to the tryptophan residues, and in determining whether these tryptophan residues lie close to the substrate-binding site.…”
mentioning
confidence: 99%